Effect of Immediate Versus Delayed Chlorhexidine Rinse on Post-Extraction Pain: A Randomized Clinical Study (Academia Journal of Medicine, 2026)
Background: Chlorhexidine mouth rinse is routinely prescribed after tooth extraction to reduce microbial load. However, the optimal timing of its use remains unclear and may influence postoperative pain. Aim: To compare the effect of immediate versus delayed chlorhexidine mouth rinse on post extraction pain following simple tooth extraction. Materials and Methods: Sixty systemically healthy patients undergoing simple tooth extraction were randomly allocated into two groups. Group I used 0.12% chlorhexidine mouth rinse immediately after extraction, while Group II initiated the rinse 24 hours post-extraction. Postoperative pain was evaluated using a Visual Analog Scale (VAS) on postoperative day 1 and day 3. Statistical analysis was performed using the independent t-test with significance set at p < 0.05. Results: Patients in the immediate rinse group reported significantly higher pain scores on postoperative day 1 compared to the delayed rinse group (p < 0.05). By postoperative day 3, pain scores decreased in both groups, with no statistically significant difference observed. Conclusion: Delaying the use of chlorhexidine mouth rinse for 24 hours after tooth extraction reduces early postoperative pain. Avoidance of immediate rinsing may help preserve the blood clot and enhance patient comfort during the initial healing period.
Keywords: Tooth extraction, chlorhexidine mouth rinse, postoperative pain, timing, oral surgery